Breeding Biology, Captive Breeding and Fry Nursing of Himped Featherback (Notopterus chilata, Hamilton-Buchanan, 1822) - Hossain, Q. Z.; Hossain, M. A.; Psrween, S. (Ecoprint: An International Journal of Ecology, 2009)
A study was conducted to observe the captive breeding performance with maturing sages and fry nursing of the threatened indigenous fish species Notopterus chitala at Arabpur fish farm (Longitude 89°12'15" E, Latitude 23°10'30" N), Jessore, Bangladesh during 1998 to 2001. The peak period of ovulation for N. chitala was found from July to August and the fish attained its first maturity at third year of age. Captive breeding is the most effective and basis process in case of N. chitala when cemented tank was used for collection of fertilized eggs, percentage of fertilization and hatching in stead of bamboo pole, plastic barrel, cemented tank and barrel made of tin. In the nursery practices live benthos, hatching of Thai punti and silver carp were used as feed of the spawn but the highest growth and survivability of the fish fry obtained by using Barbodes gonionotus (thai punti) spawn and live Tubifex sp. (benthos). Key Words: Fertilization; hatching; growth; survivability doi: 10.3126/eco.v13i0.1628 Ecoprint (An International Journal of Ecology) Vol. 13, No. 1, 2006 Page : 41-47